2011
DOI: 10.1128/jcm.02203-10
|View full text |Cite|
|
Sign up to set email alerts
|

Human Papillomavirus Type 16 Variant Analysis of E6, E7, and L1 Genes and Long Control Region in Identification of Cervical Carcinomas in Patients in Northeast China

Abstract: Human papillomavirus type 16 (HPV 16) is the primary etiology of cervical cancer, which is the second most common type of cancer in women worldwide (29). HPV 16 variants, which vary by Յ2% from HPV 16 prototype nucleotide sequences, have been identified as the following six phylogenetic branches: European (E), Asian (As), Asian-American (AA), African-1 (Af-1), African-2 (Af-2), and northern American (NA) variants (18,52). Several researchers had reported correlations between specific HPV 16 variants and persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 51 publications
5
19
1
Order By: Relevance
“…The mutation most frequently observed in LCR was G7521A in the binding site of the transcription factor YY1 (Pande et al, 2008). In this study, in accordance to other authors (Yamada et al, 1997;Schmidt et al, 2001;Kammer et al, 2002;Pande et al, 2008;Shang et al, 2011), the mutation most frequently detected in the LCR region was G7521A, found in the African lineages and most European ones. Thus, only 20% of analyzed samples presented homology with the prototype sequence.…”
Section: 1151 Mutation Detection Of E6 and Lcr Genes From Hpv 16 Asssupporting
confidence: 80%
“…The mutation most frequently observed in LCR was G7521A in the binding site of the transcription factor YY1 (Pande et al, 2008). In this study, in accordance to other authors (Yamada et al, 1997;Schmidt et al, 2001;Kammer et al, 2002;Pande et al, 2008;Shang et al, 2011), the mutation most frequently detected in the LCR region was G7521A, found in the African lineages and most European ones. Thus, only 20% of analyzed samples presented homology with the prototype sequence.…”
Section: 1151 Mutation Detection Of E6 and Lcr Genes From Hpv 16 Asssupporting
confidence: 80%
“…Previous studies have shown that some nucleotide substitutions have remarkable importance in pathogenicity [11,20,21,22]. In the present study, 16 nucleotide variations were detected.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have reported the proportion of HPV16 variants in some areas in China, and Asian and European lineages are thought to be the two major HPV16 strains in northeastern [16], central [17] and southern China [18]. However, most of these studies were based on the E6 genes or partial fragments of HPV16.…”
Section: Introductionmentioning
confidence: 94%